Effectiveness of Chemicals Used in Disinfection of Incubatories and Cattle Houses for Feeding Breeding Silkworms - Hoji, Rahmatov Normirza; Ismailovich, Bekkamov Chorshanbi (American Journal of Biology and Natural Sciences, 2024)
In clusters, farms and farms specializing in cocoons operating in our republic, during the season of worm breeding, disinfection of hatcheries and worm houses is an effective method, if compared to monochloramine, sodium hypochlorite or septoside disinfectant chemicals are used, which are 4.5-5 times cheaper and more effective. scientifically proven to be.